Clinical isolation, biofilm formation, and pathogenicity analysis of different species of the Stephanoascus ciferrii complex - Xu, Shilan; Fan, Baiyuan; Gao, Shuo; Jia, Jia; Zhang, Yan; Shen, Han; Zhou, Wanqing (Frontiers in Microbiology, 2025)
The Stephanoascus ciferrii complex, comprising Stephanoascus ciferrii, Candida allociferrii, and Candida mucifera, is an emerging fungal pathogen with increasing isolation rates and antifungal resistance. However, detailed information about clinical isolation rates and pathogenicity comparisons among the three species are lacking. In order to fill in this information gap, this study aimed to investigate and compare the clinical isolation rates and pathogenicity of the three species. Twenty-seven S. ciferrii complex strains isolated from the secretion specimens of patients admitted to Nanjing Drum Tower Hospital between 2012 and 2023 were included. According to the results of ITS sequencing, there were 15 strains of S. ciferrii, 7 strains of C. allociferrii, and 5 strains of C. mucifera. Antifungal susceptibility testing demonstrated that the S. ciferrii complex exhibited high MICs against azole antifungal agents, particularly fluconazole, while it showed lower MICs against echinocandins. S. ciferrii displayed higher MICs against caspofungin than C. allociferrii (P < 0.05). The results of biofilm quantification using crystal violet staining indicated C. allociferrii exhibited stronger biofilm-forming ability than S. ciferrii in RPMI-1640 medium (P < 0.05), but there was no significant difference between C. allociferrii and C. mucifera or between S. ciferrii and C. mucifera. The results were similar with the metabolic activity by using XTT assay. The G. mellonella larvae infection experiments revealed that the survival rates of larvae infected by strains of the S. ciferrii complex were 60%, 50%, and 48% at 24 h, 48 h, and 72 h, respectively. Furthermore, the G. mellonella larvae lethality caused by C. allociferrii and C. mucifera were significantly higher than that caused by S. ciferrii (P < 0.001). This study is the first to describe and compare the pathogenicity and biofilm formation ability of the three species of S. ciferrii complex in the clinical context. Our research reveals the high prevalence of S. ciferrii in the complex and elucidates the correlation between fungal drug resistance, biofilm formation, and virulence, thus providing essential empirical evidence for further study of the clinical pathogenic characteristics of each species in the complex and treatment strategies.